Associations Among Monoamine Neurotransmitter Pathways, Personality Traits, and Major Depressive Disorder - Shao, Xiaojun; Zhu, Gang (Frontiers in Psychiatry, 2020)
Major depressive disorder (MDD) is a complex psychiatric disease requiring multidisciplinary approaches to identify specific risk factors and establish more efficacious treatment strategies. Although the etiology and pathophysiology of MDD are not clear until nowdays, it is acknowledged that they are almost certainly multifactorial and comprehensive. Monoamine neurotransmitter system dysfunction and specific personality traits are independent risk factors for depression and suicide. These factors also demonstrate complex interactions that influence MDD pathogenesis and symptom expression. In this review, we assess these relationships with the aim of providing a reference for the development of precision medicine.